Combination Therapy of Ipilimumab and Nivolumab-associated Toxic Epidermal Necrolysis (TEN) in a Patient With Metastatic Melanoma: A Case Report and Literature Review. Issue 3 (April 2020) - Logan, Ian T.; Zaman, Saman; Hussein, Lama; Perrett, Conal M.
Abstract : Ipilimumab and nivolumab are immune checkpoint inhibitors used in the treatment of metastatic melanoma. The authors report the case of a 62-year-old white male individual with metastatic choroidal melanoma who had commenced adjuvant systemic treatment with combination checkpoint inhibitor therapy of intravenous ipilimumab (anti-cytotoxic T-lymphocyte antigen-4) and nivolumab (anti-programmed cell death-1) at 3-week cycle intervals. On day 4 after the second cycle, he developed an acute widespread rash. On examination there was confluent erythema with bullae and epidermal loss over 60% of the body surface area, with severe oral mucosal ulceration. A clinical diagnosis of toxic epidermal necrolysis (TEN) was made and he was transferred to the intensive care unit. Despite active treatment, he deteriorated systemically and died from multiorgan failure. This is the first reported case of TEN associated with nivolumab and ipilimumab dual therapy for metastatic uveal melanoma. Monotherapy improves survival in metastatic melanoma, but dual therapy has shown a greater mortality benefit at 3 years. Although the literature demonstrates case reports of Stevens-Johnson syndrome and TEN in association with nivolumab, ipilimumab has generally been regarded as a "safe" treatment with regard to severe cutaneous adverse reactions. With the increased use of immunotherapies, it is important to plan the management and early recognition of drug-related skin toxicity. This is of greatest concern during treatment initiation and with the higher risk associated with combination therapy. Reporting of adverse events and infrequently encountered complications with systemic biologic treatments will augment pharmacovigilance and improve the stratification of patients to treatments.